Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 2001
DOI: 10.1115/2001-gt-0352
|View full text |Cite
|
Sign up to set email alerts
|

Probing Into the Connotation of Sweep Aerodynamics of Transonic Fans and Compressors

Abstract: Theory researches, numerical analyses and experiment studies of sweep aerodynamics in turbo-machinery had rapidly developed during the 1990s. Taking a low-aspect-ratio, high-loaded axial flow transonic rotor as the baseline, this paper attempts to probe the connotation of sweep aerodynamics of transonic fans and compressors. The definition of sweep angle was discussed. Flow field, key factors that affect structures of flow fields, linkage between leading edges as well as flow field structures in swept rotors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Use of the axial location is convenient during the airfoil design process [16] because the change in the axial location impacts the shifting of the sections grav- ity center location, which again impacts blade structure frequency and stresses. In most of the sweep airfoil studies, the airfoil chord lengths were changed in some sections [9,11] and the locations of the airfoil base section were also changed, making it di©cult to see the aerodynamic sweep e¨ects whether it is coming from the sweep or from the section changes. In this study, the base sections were ¦xed.…”
Section: Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of the axial location is convenient during the airfoil design process [16] because the change in the axial location impacts the shifting of the sections grav- ity center location, which again impacts blade structure frequency and stresses. In most of the sweep airfoil studies, the airfoil chord lengths were changed in some sections [9,11] and the locations of the airfoil base section were also changed, making it di©cult to see the aerodynamic sweep e¨ects whether it is coming from the sweep or from the section changes. In this study, the base sections were ¦xed.…”
Section: Calculationsmentioning
confidence: 99%
“…The study by Xing et al [11] showed that a stall margin of the back-sweep is about the same as that of an unswept rotor blade. These studies show that the e¨ect of sweep on transonic compressors is not fully understood.…”
Section: Introductionmentioning
confidence: 97%
“…Conversely, the forward sweep could increase the stall margin. The study by Xing et al [12] showed that a stall margin of the back sweep is about the same as that of the unswept rotor blade. Clearly, the effects of sweep on transonic compressors are not fully understood.…”
Section: Introductionmentioning
confidence: 96%
“…There are not many detailed descriptions of sweeps and whether other design parameters change or not when sweeps were implemented. Most studies [10][11][12] did not report whether the test flow boundary conditions were the same for all sweeps and unsweeps. Much research still needs to be done to better understand sweep blades in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Hah, Copenhaver, Puterbaugh and Wadia [6] used aerodynamic sweep to control shock structure and secondary flow field of a transonic compressor rotor. Denton and Xu [7], Xu and Chen [8], Xing, Zhou and Zhao [9] through numerical computational method studied the sweep effect on performance in fans and compressors. Therefore, it is seem clearly that study on blade sweeping has become one of the important research projects.…”
Section: Introductionmentioning
confidence: 99%